2017
DOI: 10.1097/iop.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Ruptured Periorbital and Orbital Dermoid Cysts

Abstract: Persistent inflammation is uncommon after surgical rupture of dermoid cysts, but likely after spontaneous rupture. Older age and bony attachment are risk factors for cyst rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…In a retrospective multicentric study, cases from 3 oculoplastic centers (Queen Victoria Hospital, East Grinstead, United Kingdom; King Abdulaziz University Hospital, Riyadh, Saudi Arabia; South Australian Institute of Ophthalmology and Visual Sciences, Australia) over a 10-year period, 29 of the total 86 cases were ruptured and only 2 were reported as spontaneous rupture. In the same study, it was pointed out that persistent inflammation was more pronounced after spontaneous rupture [11]. Our case was compatible with inflammation by ruptured dermoid cyst condition, in which infection and other causes are eliminated.…”
Section: Case Reportsupporting
confidence: 80%
See 1 more Smart Citation
“…In a retrospective multicentric study, cases from 3 oculoplastic centers (Queen Victoria Hospital, East Grinstead, United Kingdom; King Abdulaziz University Hospital, Riyadh, Saudi Arabia; South Australian Institute of Ophthalmology and Visual Sciences, Australia) over a 10-year period, 29 of the total 86 cases were ruptured and only 2 were reported as spontaneous rupture. In the same study, it was pointed out that persistent inflammation was more pronounced after spontaneous rupture [11]. Our case was compatible with inflammation by ruptured dermoid cyst condition, in which infection and other causes are eliminated.…”
Section: Case Reportsupporting
confidence: 80%
“…Dermoid cysts constitute 5% of all orbital lesions in childhood [3]. These lesions are assumed to originate from ectodermal tissue deviating from sequencing that occurs when suture lines are closed during embryonic development [4,5]. Cyst rupture or leakage of the cyst content is one of the rare causes of orbital inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…En block removal of the orbital dumbbell dermoid cysts is often difficult as they are tightly adhered to the bones at the frontozygomatic suture. 1 , 2 , 6 Therefore, an accidental cyst rupture occasionally occurs, which also happened in the present case. Several surgical techniques have been reported to avoid unintended surgical rupture.…”
Section: Discussionsupporting
confidence: 69%
“…They sometimes rupture spontaneously, which causes inflammation of the eyelids and orbits. 2 A complete removal is mandatory to avoid postoperative recurrence and inflammation. 3 …”
Section: Introductionmentioning
confidence: 99%
“…2 In our series intraoperative rupture occurred in significantly more number adults as compared to children. Siah et al 24 reported that the risk of persistent inflammation is small in surgically ruptured cyst, where the spillage of cyst contents has been dealt with meticulously. 24 Furthermore, in cases of spontaneous cyst rupture there is a high risk of persistent inflammation, hence supporting the benefit of operating early.…”
Section: Discussionmentioning
confidence: 99%